2015
DOI: 10.5114/fn.2015.56552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with branched chain amino acids and ornithine aspartate on plasma ammonia and central fatigue during exercise in healthy men

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Notably, to the best of our knowledge, this is the first study adopting a validated and reliable HIEC protocol [26] for these purposes. Indeed, other protocols have been used to determine similar end-points in the past [20,53], but it is worth noting that they had not been previously and specifically validated. The major finding of this study is that a single intake of FP is capable of attenuating RPE, and that its prolonged 9w consumption according to manufacturer's recommendations not only augments RPE-attenuating capacity, but also improves TTE and TRIMP, which both reflect the capacity to sustain training loads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, to the best of our knowledge, this is the first study adopting a validated and reliable HIEC protocol [26] for these purposes. Indeed, other protocols have been used to determine similar end-points in the past [20,53], but it is worth noting that they had not been previously and specifically validated. The major finding of this study is that a single intake of FP is capable of attenuating RPE, and that its prolonged 9w consumption according to manufacturer's recommendations not only augments RPE-attenuating capacity, but also improves TTE and TRIMP, which both reflect the capacity to sustain training loads.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these findings, researchers have turned their attention to the study and development of supplements containing BCAA alone or combined with specific substances (such as CHO), assessing the efficacy of their association [15,20]. Several recent investigations have shown BCAA supplementation to positively affect prolonged exercise under specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…34,52,53 Considering that ammonia is toxic and its buildup is detrimental to the activity of several organ systems, such as the CNS, 54,55 the hyperammonemia state, common in liver diseases, contributes to the development of hepatic encephalopathy and the worsening of clinical conditions. 56,57 In addition, in chronic hepatopathies, there is a reduction in the plasma 161 concentration of BCAA and an increase in the plasma concentration of the aromatic amino 162 acids (AAA) tryptophan, phenylalanine, and tyrosine. 58 This imbalance in BCAA/AAA ratio, also called Fischer's ratio, is associated with the development of hepatic encephalopathy and progression of liver diseases.…”
Section: Oxidation Of Bcaa By the Brainmentioning
confidence: 99%
“…One factor that may have supplanted the ergogenic effect of BCAA is the production of ammonia, a neurotoxic substance 19 derived from the metabolism of these amino acids. [20][21][22][23] This assumption may also explain the reduction in force during the pre-exercise MVC ISO in subjects supplemented with BCAA. Dong-Hee et al (2013) 22 showed a higher ammonia concentration at 40 min after the ingestion of a single dose of BCAA (80 mg.kg -1 ).…”
Section: Discussionmentioning
confidence: 99%